1998
DOI: 10.1111/j.1399-302x.1998.tb00731.x
|View full text |Cite
|
Sign up to set email alerts
|

Ribotype diversity of Actinomyces With similar intraoral tropism but different types of N‐acetyl‐β‐d‐galactosamine binding specificity

Abstract: Sixty-three isolates of Actinomyces naeslundii genospecies 1 and 2 and Actinomyces odontolyticus from three subjects clustered into 22 ribotypes. Unique ribotypes were found in the subjects and within individual tissue sites (bucca, tooth and tongue). A odontolyticus ribotypes shared tongue-specific binding properties, while those of genospecies 1 and 2 from buccal and tooth surfaces shared different types of N-acetyl-beta-D-galactosamine binding specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…It is noteworthy that saliva which favors the binding of S. mutans appears to occur at low frequencies (Table 1), and only few individuals are colonized with high numbers (Carlsson, 1988). Also, APRP binding is highly prevalent among early Actinomyces (Str6mberg et al, 1996;Hallberg et al, 1997) and streptococci (Hsu et al, 1994), both of which colonize most individuals in high numbers (Nyvad and Kilian, 1987). The agglutinin biological activity coincided with the S. mutans binding capacity of the three saliva samples.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…It is noteworthy that saliva which favors the binding of S. mutans appears to occur at low frequencies (Table 1), and only few individuals are colonized with high numbers (Carlsson, 1988). Also, APRP binding is highly prevalent among early Actinomyces (Str6mberg et al, 1996;Hallberg et al, 1997) and streptococci (Hsu et al, 1994), both of which colonize most individuals in high numbers (Nyvad and Kilian, 1987). The agglutinin biological activity coincided with the S. mutans binding capacity of the three saliva samples.…”
Section: Discussionmentioning
confidence: 89%
“…The acidic, basic, and glycosylated proline-rich proteins (PRPs) are major and highly polymorphic salivary constituents which mediate bacterial adherence to oral surfaces (Gibbons and Hay, 1988;Gibbons, 1989;Lamkin and Oppenheim, 1993). Members of the genera Streptococcus and Actinomyces, both of which constitute a major portion of early dental plaque (Nyvad and Kilian, 1987), therefore bind avidly to acidic PRPs (APRPs) (Gibbons, 1989;Hsu et al, 1994;Strormberg et al, 1996;Hallberg et al, 1997). The APRP receptor determinants for the A. naeslundii strain LY7 and the S. gordonii strain Blackburn have been delineated to the ProGlndipeptide-a repetitive structure in the carboxy-terminal domain of APRPs and the statherin protein (Gibbons et al, 1991).…”
Section: Introductionmentioning
confidence: 98%
“…Among various Actinomyces spp., strains belonging to A. naeslundii remain the most heterogeneous (38). Previous workers have used different methodology to study the genetic diversity of this species, including genomic DNA fingerprinting (6, 30), ribotyping (6, 19), PCR‐RFLP with different endonuclease (26, 34), and arbitrarily primed‐polymerase chain reaction (AP‐PCR) (30).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have also reported on the intra- and inter-species diversities of A. naeslundii and A. oris , as A. naeslundii genospecies 1 and 2 using DNA fingerprinting [11], ribotyping [5], [12], amplified 16S ribosomal DNA restriction analysis (ARDRA) [4], [13], DNA probes [14], sequence analysis of fimA genes [9] and REP-PCR amplicons analysis [10]. All these studies have demonstrated extensive heterogeneity within each taxon.…”
Section: Introductionmentioning
confidence: 99%